Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 5480 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Pogonocichla stellata (Vieillot, 1818)" ] } The dataset includes 5480 records from 45 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004858-160803222355964/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences